Corrigendum to “Energy saving potential analysis applying factory scale energy audit – A case study of food production” [Heliyon 9 (3), (March 2023) Article e14216] - Derar, Al Momani (2023)
In the original published version of this article, the authors have requested to change the institutional information. The institutional information of the authors have been updated. The correct version of the institutional information of the authors can be found below: Mohammed I. Abuashour institutional information has been changed from: Renewable Energy Centre, The Hashemite University, Zarqa, 13115, Jordan to: Renewable Energy Centre, Electrical Engineering Department, Faculty of Engineering, The Hashemite University, Zarqa, Jordan. And. Haris M. Khalid L institutional information has been changed from: Department of Electrical and Electronics Engineering, Higher Colleges of Technology, Sharjah 7947, United Arab Emirates To. College of Engineering and Information Technology, University of Dubai, Academic City 14143, Dubai, United Arab Emirates The authors/publisher apologize for the errors. Both the HTML and PDF versions of the article have been updated to correct the errors.